The Lived Experience of Family Support Among Women During and After Childbirth in Jordan: A Phenomenological Study - Amal MT. Ababneh RN, MSN; Nour Alrida RN, MSN; Manar Abu-Abbas RN, PhD; Ahmad Rayan RN, PhD; Yasmeen Abu Sumaqa RN, PhD; Sajeda Alhamory RN, MSN, PhD; Basheer Al-Zu'bi RN, MSN (SAGE Publishing, 2024)
Introduction Many studies highlight the importance of family support in enhancing the experience of childbirth among women. Objective This qualitative study aimed to describe the lived experience of family support from the perspective of women during and after childbirth in the Jordanian context Methods A qualitative descriptive phenomenological approach was used to explore the experiences of women's family support in the context of their childbirth experiences. A total of 11 Jordanian women participated in the study. Face-to-face semi-structured interviews were conducted to collect data. Results Four major themes emerged from the data describing family support provided to women during and after childbirth. These themes were family support during childbirth, family support in the postpartum period, importance of family support during and after childbirth, and challenges related to receiving family support. Supportive family members primarily included the husband, the woman's family, and the family-in-law, according to the traditions inherited in the Jordanian context and culture. Conclusion The study findings could help maternal health professionals screen pregnant women who are at risk of receiving low family support, contribute to developing effective interventions regarding family-centered care, and enhance the overall childbirth experience for women in Jordanian cultural contexts.